“Haemolacria” – The Bleeding Eye – A Case Report (Homoeopathy for All, 2024)
Haemolacria is an exceedingly rare  condition. Due to low incidence and  limited literature, the prevalence  and predilection of haemolacria for  a specific gender, race, or age is  not known. The pathophysiology  of haemolacria depends on  the case-specific cause of this  condition. Homoeopathy can help  in haemolacria, it is evident from  this case of a girl age 11 years who  was suffering from haemolacria  and treated with in 1year with  Homoeopathic similimum which  was selected on the basis of  individualisation.
Keywords: Homoeopathy; haemolacria; Individualisation